2019
DOI: 10.14474/ptrs.2019.8.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical intervention on cutaneous sensory change and pressure pain threshold in the same spinal segment of myofascial pain

Abstract: The purpose of this study was to identify whether cutaneous sensory (CS) changes induced by mechanical intervention (MI) increases the trigger point threshold of the same spinal segment as well as to investigate the relationship between the amounts of change in CS pressure pain thresholds (PPT). Design: Randomized controlled trial. Methods: Thirty-nine persons with myofacial pain (MFP) were recruited in this experiment. The subjects consisted of 20 men and 19 women (age 20-39). MI was applied on the subjects u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In addition, according to the effect size results of this present study, the effect of STM showed more than a moderate effect in all variables except for PCS-K. As a basis for interpreting the results of this study, it has been reported that STM, which is included in massage therapy, induces a decrease in cortisol and an increase in serotonin, dopamine, and oxytocin in response to stressful experiences [51][52][53]. Similarly, an increase in the amount of change in superficial sensation due to the neuroplastic effect leads to an increase in the amount of change in PPT in the same spinal segment [54], and the decrease in superficial sensation could continue even after treatment is completed [55].…”
Section: Discussionmentioning
confidence: 63%
“…In addition, according to the effect size results of this present study, the effect of STM showed more than a moderate effect in all variables except for PCS-K. As a basis for interpreting the results of this study, it has been reported that STM, which is included in massage therapy, induces a decrease in cortisol and an increase in serotonin, dopamine, and oxytocin in response to stressful experiences [51][52][53]. Similarly, an increase in the amount of change in superficial sensation due to the neuroplastic effect leads to an increase in the amount of change in PPT in the same spinal segment [54], and the decrease in superficial sensation could continue even after treatment is completed [55].…”
Section: Discussionmentioning
confidence: 63%
“…Stimulation applied to the topical area inhibits the excitation of A-delta and C fibers, while it excites the harmless receptors such as A-alpha and A-beta fibers, which blocks the synapses that transmit pain infromation to higher center neurons, thus reducing pain transmission and altering tissue sensitivity. Cutaneous sensory changes induced by mechanical stimulation showed significant results of increasing PPT [32]. There were significant results in hamstring flexibility, pressure pain threshold, and muscle tension in both the extracorporeal shock wave group and the extracorporeal shock wave group that has included stretching techniques [33].…”
Section: Discussionmentioning
confidence: 98%
“…Due to the high-density free nerve endings found in the fascia, part of the sympathetic nervous system, a more relaxed parasympathetic response is displayed. Additionally, Ruffini corpuscle activity is seen due to the heat generated by the foam roller and soft tissue stimulation, which improves dynamic balance ability and range of motion 32 35 .…”
Section: Discussionmentioning
confidence: 99%